Conventional and microwave synthesis, spectral, thermal and antimicrobial studies of some transition metal complexes containing 2-amino-5-methylthiazole moiety - A.P. Mishra; Rajendra K. Jain (Journal of Saudi Chemical Society)
Schiff base metal complexes of Cr(III), Co(II), Ni(II) and Cu(II) derived from 5-chlorosalicylidene-2-amino-5-methylthiazole (HL1) and 2-hydroxy-1-naphthylidene-2-amino-5-methylthiazole (HL2) have been synthesized by conventional as well as microwave methods. These compounds have been characterized by elemental analysis, FT-IR, FAB-mass, molar conductance, electronic spectra, 1H-NMR, ESR, magnetic susceptibility, thermal, electrical conductivity and XRD analyses. The complexes exhibit coordination number 4 or 6. The complexes are coloured and stable in air. Analytical data reveal that all the complexes exhibit 1:2 (metal:ligand) ratio. IR data show that the ligand coordinates with the metal ions in a bidentate manner through the phenolic oxygen and azomethine nitrogen. FAB-mass and thermal data show degradation pattern of the complexes. The thermal behaviour of metal complexes shows that the hydrated complexes lose water molecules of hydration in the first step; followed by decomposition of ligand molecules in the subsequent steps. XRD patterns indicate crystalline nature for the complexes. The Schiff bases and metal complexes show good activity against the Gram-positive bacteria; Staphylococcus aureus and Gram-negative bacteria; Escherichia coli and fungi Aspergillus niger and Candida albicans. The antimicrobial results also indicate that the metal complexes are better antimicrobial agents as compared to the Schiff bases.